Aspects of Jogo Phonology - Williams, E. (University Of Ghana, 2018)
Jogo is one of the three Mande languages (Bisa and Wangara/Dyula) spoken in Ghana. Jogo is a dialect of the language commonly known as Ligbi, spoken in Banda and Menji, in the Banda and Tain Districts respectively. The other dialects of Ligbi are Weila, of Namasa; Ntɔleh of Kwametenten and Ntɔgɔleh (also referred to as Numu/Atumfuɔkasa) of Brohani, all of the Tain District of the Brong Ahafo Region of Ghana. This thesis investigates the sound system, the syllable type, and some phonological processes in Jogo. Data is mainly from primary sources. The Summer Institute of Linguistics Comparative African WordList (SIL CAWL 2) comprised of 1700 words was used to elicit the data. Recorded conversations on FM programs were obtained, folk tales, proverbs and riddles were recorded with a handheld digital recorder. A 200-item Swadesh word list was also employed to collect data and compare the dialect continuum of the three (3) main dialects of Ligbi. The thesis is divided into five main chapters. The first chapter is the introduction, which gives a socio-economic information about the people and language, the objective and methodology. Chapter two is an overview of the literature review and the theoretical framework employed to analyze the data. Chapter three focuses on the sounds of Jogo. The study employs the linear phonology approach to investigate the phonemic inventory of Jogo. Chapter four investigates some phonological processes such as syllable structure processes which include elision, and epenthesis (including a floating consonant). Chapter five, which is the final part of the thesis concludes with a summary and recommendation of the study. Dakubu (1988:161) argues that Jogo has seven (7) vowel system, interestingly the findings in this study show that Jogo has nine (9) oral vowels, and seven (7) nasal counterparts, and finally twenty-seven (27) consonants, including labiovelars. Other findings show that the syllable types are V, CCV, CV, CV:, CrV, and CVC/ CVN. The study indicates that phonological processes such as nasalization, labialization, palatalization, and homorganic nasal assimilation occur in Jogo.
MPhil. Linguistics
Keywords: Jogo; Phonology